The Law of Torts in New Zealand - McLay, G (Victoria University of Wellington Law Review, 1997)
This article is a book review of The Law of Torts in New Zealand (2ed, Wellington, 1997) (Todd (general editor), Hughes, Burrows, Chambers, Hawes, Bedggood, Beck) pp 1316 + xcviii, 144 (inclusive of GST). McLay notes that an updated edition of a torts textbook was welcome at the time, providing a useful account of tort law developments at the time of writing by commenting on how the book explores such issues. While elements of the book are praised, McLay notes that the relationship between tort and contract is not developed in the book as it might have been. It is also argued that the book does not go as far as it might have in the area of government liability in negligence, including in the accident compensation chapter. McLay concludes that tort theory is secondary in this book, resulting in a lack of contextual understanding of tort law in New Zealand and the direction it is headed.